2013
DOI: 10.1038/srep02215
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Polarization in Nanocrystalline Hydroxyapatite Thin Films on Silicon

Abstract: Hydroxyapatite nanocrystals in natural form are a major component of bone- a known piezoelectric material. Synthetic hydroxyapatite is widely used in bone grafts and prosthetic pyroelectric coatings as it binds strongly with natural bone. Nanocrystalline synthetic hydroxyapatite films have recently been found to exhibit strong piezoelectricity and pyroelectricity. While a spontaneous polarization in hydroxyapatite has been predicted since 2005, the reversibility of this polarization (i.e. ferroelectricity) req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(75 citation statements)
references
References 31 publications
1
72
0
2
Order By: Relevance
“…It is interesting that, this value is fully in line with the data obtained earlier from cluster models (P ~ 0.005 C/m 2 ) [30]. Corresponding piezoelectric coefficient for this case on the order of dyy = d33 ~ 15.7 pC/N ~ 15.7 pm/V was estimated in [30], which is very close to value d33 ~ 16 pm/V measured in [50], and is twice larger than the value of the experimentally measured in [51] effective piezoelectric coefficient d33eff ~ 8 pm/V, which varies significantly from grain to grain. This deviation was explained in [43] by polar properties variation for different grains: piezoelectric contrast (observed in Ref.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…It is interesting that, this value is fully in line with the data obtained earlier from cluster models (P ~ 0.005 C/m 2 ) [30]. Corresponding piezoelectric coefficient for this case on the order of dyy = d33 ~ 15.7 pC/N ~ 15.7 pm/V was estimated in [30], which is very close to value d33 ~ 16 pm/V measured in [50], and is twice larger than the value of the experimentally measured in [51] effective piezoelectric coefficient d33eff ~ 8 pm/V, which varies significantly from grain to grain. This deviation was explained in [43] by polar properties variation for different grains: piezoelectric contrast (observed in Ref.…”
supporting
confidence: 79%
“…This deviation was explained in [43] by polar properties variation for different grains: piezoelectric contrast (observed in Ref. [51]) is registered only in some polar grains (ordered monoclinic HAP) and is averaged with other non-polar grain contribution (disordered hexagonal HAP). The resultant contrast turns out to be nearly twice less than the calculated value (corresponding to the case when all the grains are polar).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typical results of these analyses confirmed that these films were phase pure and nanocrystalline. An earlier investigation has also established the polar nature of these films, which exhibited natural piezo, pyroelectricity [14] and ferroelectrocity [15].…”
Section: Methodsmentioning
confidence: 96%
“…23 teeth, 24 cartilage, 25 diphenylalanine nanotubes, 26 amino acids, 27 hydroxyapatite, 28 and other polar materials including a large number of ferroelectric perovskites. 29,30 In this work, we report on sufficiently strong piezoelectricity and switchable polarization in thymine microcrystals grown from the solution.…”
Section: Introductionmentioning
confidence: 99%